Applying value stream mapping in packaging industry: a case study - O Joochim; S Jungthawan (My University, 2021)
Abstract The aim of this paper is to increase the productivity of a packaging manufacturing process by using lean manufacturing technique. The current system of this packaging manufacturing process has been mapped using Value Stream Mapping (VSM) tool. This tool is a lean manufacturing tool, and the wastes in the current system are identified. The case study shows how the VSM tool has been utilized for identifying and decreasing the waste in the manufacturing process resulting of the total cost saving of 3,247,251 Thai Baht (THB) per year.
Keywords: Value stream mapping; Manufacturing process; Manufacturing; Quality and Supply Management